European Union Military Missions and the War in Ukraine: Moving beyond the Jus ad Bellum Framework - Svicevic, Marko (Polish Review of International and European Law, 2024)
Since the commencement of the Russian invasion of Ukraine on 24 February 2022, States and regional/international organisations have taken a number of measures both in favour of Ukraine and against the Russian Federation. In the context of support provided to Ukraine, these measures have varied, from financial and humanitarian aid, to weapons supplies and intelligence sharing. Despite the varying degrees of support, no State has yet claimed direct reliance on the jus ad bellum regime, the legal framework which would allow for military responses to the ongoing situation in Ukraine (most notably under the regime of collective self-defence). This paper considers the implications of support given to Ukraine by the European Union, considering its historical role in military and training operations across the Balkans and Africa. It questions whether and to what extent the jus ad bellum regime has been intentionally avoided to prevent escalation. In considering the ongoing support, the paper then examines whether avoidance of the jus ad bellum regime can be considered a move beyond the regime itself, or whether the various and increasing intensity of support ought to be considered a development of the regime itself.